STUDY OF PHOTOCATALYTIC HYDROGEN PRODUCTION OVER Ni-DOPED ZnO AND TiO₂ PHOTOCATALYSTS VIA CHEMICAL STABILIZATION - Frendi Maulana; Yohanes Engge (PT. Jurnal Center Indonesia Publisher, 2026)
This study synthesized Ni-doped ZnO (Ni0.05Zn0.95O) and TiO2 (Ni0.05Ti0.95O2) via immersion-assisted coprecipitation for hydrogen production. UV-Vis confirmed bandgap reduction to 2.87 eV (ZnO) and 2.82 eV (TiO2), enabling visible light activity. XRD and SEM verified Ni incorporation and a significant reduction in crystal size (to 21 nm). To mitigate rapid particle sedimentation (25 min), sodium silicate was applied as a dispersant, successfully extending suspension stability to 4 hours. Notably, this chemical stabilization maintained a lower reactor temperature (49°C) compared to mechanical stirring (52°C), preventing efficiency loss due to thermal effects. Ni0.05Zn0.95O exhibited the highest photocatalytic activity, attributed to its superior Ni atomic composition. This research demonstrates that combining Ni-doping with chemical dispersion effectively optimizes both the electronic and physical properties of photocatalysts for enhanced hydrogen harvesting.